The First Comprehensive Examination of Male Morphometrics and the Operational Sex Ratio of the Black Sea Turtle (Chelonia mydas agassizii) Population in Colola, Michoacan, Mexico - Carlos Delgado-Trejo; Miguel Ángel Reyes-López; David Guillermo Pérez-Ishiwara; Ricardo Lemus-Fernández; Fátima Yedith Camacho-Sánchez; Cutzi Bedolla-Ochoa (Animals)
Body size is one of the most important traits in the life history of vertebrates. In this work, we analyzed the morphometric traits of breeding males of the eastern Pacific green sea turtle population known as the black sea turtle on the coast of Michoacan, Mexico. The morphometric analysis indicates that males have the smallest body size compared to other males in other Chelonia populations. The size of male black sea turtles is even smaller (by 15.2 cm in average CCL) in carapace curve length (70.5 cm CCL) than females (85.7 CCL) of the same population. This suggests that males reach maturity at an earlier age than females and would have implications for mating success. The assessment of the operational sex ratio was conducted over a multi-year period (2004, 2009, 2017, and 2023). From a total of 336 h of observation, we identified 653 mating groups containing 1986 males and 669 females. The estimated operational sex ratio (OSR) during the study period was 2.96 males for every female. Among the mating groups, 34.3% consisted of only one male, while 65.7% included two or more males, with the number of males per female ranging from 2 to 17. The analysis revealed that there are interannual and monthly variations in OSR values, with observations showing a range from 2.3:1 (male to female) in 2023 to 4.3:1 (male to female) in 2009. The OSR variations show an evolving trend that can inform future strategies. In September, the ratio was 2.8:1, which changed to 3:1 in October and November, and then reached 3.3:1 in December (male/female). This gradual increase provides a clear opportunity to delve deeper into these dynamics and take proactive measures to address them positively.